Enhancing Personal and Environmental Factors to Nurture the Inclusion of Italian Learners in Malta: A Case Study - Barbara Baschiera; Sandro Caruana (Pensa MultiMedia, 2023)
In order to investigate how the combination of experiences, relationships, activities and initiatives act in unison, facilitating inclusive processes on some occasions and creating obstacles to it on others, in this contribution on Italian migrant leaners in Malta we adopt a biopsychosocial perspective, inspired by the WHO's ICF-CY anthropological model. We interviewed ten parents/guardians to obtain insights on personal and environmental factors that affect inclusion in Maltese Secondary schools. Our findings reveal that parents/guardians relate personality factors to successful inclusion (e.g. adaptability, entrepreneurship and sociability), as well as involvement in extra-curricular activities. The Maltese schooling context, a competitive approach to learning, traditional teaching methodologies and lack of support represent barriers to inclusion. The holistic model we adopt shows that to guarantee quality inclusive pedagogies initial teacher education and continuing professional development must be addressed. Maltese schools must build better bridges with families, embracing inclusive perspectives from an eco-systemic educational viewpoint.